2016
DOI: 10.1039/c6ta03688k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic swellable metal–organic framework encapsulated Pd nanoparticles as an efficient catalyst for Cr(vi) reduction

Abstract: Controllable integration of metallic nanoparticles and metal-organic frameworks (MOFs) may create a new material with multifunctional applications. In this work, an emerging type of core-shell nanostructure, in which the metallic Pd nanoparticles cores were encapsulated by the MOF (ZIF-67) shells, was facilely synthesized through an impregnationreduction process. The as-synthesized Pd@ZIF-67 material, with highly dispersed Pd nanoparticles encapsulated in the porous ZIF-67 structure, exhibited favorable cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…For example, Jiang and co‐workers have reported the incorporation of Pd nanoparticles within a MOF for the catalytic reduction of 4‐nitrophenol . Yu and co‐workers demonstrated that the encapsulation of Pd nanoparticles within a MOF results in a highly efficient Cr VI reduction activity . Meanwhile, several methods have been developed to create hybrid MOFs containing two or more components or functions for the enhanced utilizations of MOFs by providing extra stability or functionality .…”
Section: Methodsmentioning
confidence: 99%
“…For example, Jiang and co‐workers have reported the incorporation of Pd nanoparticles within a MOF for the catalytic reduction of 4‐nitrophenol . Yu and co‐workers demonstrated that the encapsulation of Pd nanoparticles within a MOF results in a highly efficient Cr VI reduction activity . Meanwhile, several methods have been developed to create hybrid MOFs containing two or more components or functions for the enhanced utilizations of MOFs by providing extra stability or functionality .…”
Section: Methodsmentioning
confidence: 99%
“…The resulting composites exhibit favorable catalytic performance, as demonstrated by the short time of complete reduction of Cr(VI) into Cr(III). Importantly, Yu et al [ 152 ] proposed a reasonable mechanism for the catalytic reduction of Cr(VI) into Cr(III), as evidenced by a series of experiments. Formic acid is first adsorbed on the surface of metal NPs, and is then is dehydrogenated to produce H 2 and CO 2 , according to Equation (1).…”
Section: Catalysis Applicationsmentioning
confidence: 99%
“…Among the physical, chemical, and biological technologies that are applied for the removal of pollutants, heterogeneous catalysis, including photocatalysis, has been demonstrated to be an efficient, economical, and green technique to degrade pollutants into easily biodegradable or less toxic compounds. Recently, MOF based composites with noble metal NPs, metal oxide/sulfides, GO, and other compounds have been proved to be a new class of catalysts, which are usable in the catalytic degradation of organic pollutants and Cr(VI) [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ].…”
Section: Catalysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid ZIF materials are also attracting many scientists because of their potential applications. In particular, the combination of ZIFs and metal nanoparticles can create a new material that integrates the advantages of each individual component, such as synthesis of Pd/ZIF-8 material using a simple route with liquid impregnation and chemical reduction methods [26], synthesis of Pd@ZIF-67 for Cr reduction from highvalent ion(VI) to low-valent ion(III) with high catalytic activity and excellent cycle durability [27], and synthesis of Ag/ZIF-67 using a simple impregnation method applying for degradation reaction of methyl orange in the presence of hydrogen peroxide with excellent efficiency [28].…”
Section: Introductionmentioning
confidence: 99%